Debt Collection Violations in Financial Technology in a Cyber-ethic and Legal Perspective - Wawan Edi Prastiyo; I Dewa Made Suartha (Ikatan Sarjana Komunikasi Indonesia, 2021)
The presence of financial technology (Fintech) on the one hand makes it easy for people to obtain credit, while on the other hand, it creates various problems. In this study, two issues will be discussed, namely the application of cyber-ethic in protecting personal data and legal issues in collecting debt on Fintech. This research is a qualitative research. Data in the study were collected by means of literature study and presented descriptively and analytically. Cyber-ethic is implemented by protecting personal data. It is a transformation of traditional ethics in cyberspace. The cyber-ethic is very necessary in the business world. The application of cyber-ethic in the world of Fintech is carried out by protecting the personal data of both borrowers and third parties. Cyber-ethic violations have implications for breaking the law. Some of the billing violations on the Fintech business are sexual harassment, defamation, threats and stalking. Borrowing customers are powerless to face debt collectors’ behavior, because the debt collectors use the borrowers’ personal data to exert psychological pressure on the debtors to pay according to the bills determined unilaterally by Fintech. This condition usually occurs in illegal Fintechs that are not registered with the Financial Services Authority.